Effect of Artemisia aucheri on Regression of Atherosclerotic Plaque in Rabbits - N Jafari Dinani; S Asgari; H Madani; GHA Naderi; P Mahzuni (Institue of Medicinal Plants, ACECR, 2009)
Background: Atherosclerosis which is the most common risk factor for CHD is caused by a gradual deposition of lipids in large and small arteries. Nowadays regression and suppression of atherosclerotic lesion is one of the candidate approach for prevention of atherosclerotic complication. Objective: Whereas large majority of people use herbal medicine for treatment, this study was designed to evaluate the effects of A. aucheri on regression of atherosclerosis in atherosclerotic rabbits. Methods: Twenty rabbits were randomly divided into four groups of five each and treated 3-months as follows: 1: normal diet for 3- month, 2, 3 and 4: Hypercholesterolemic diet (HCD) for 2- month. One group (2) killed after this period and two groups (3 and 4) received normal dietand normal diet + A. aucheri (100 mg. kg-1 .day-1) respectively for an additional 1 - month (regression period). Biochemical factors (total cholesterol, LDL-cholesterol, HDL- cholesterol and triglycerides) were measured at first, end of second and third month. At the end of the study, animals killed and aortas were removed for assessment of atherosclerotic plaques. Results: Normal diet in regression period improved lipid profile but the animals in this group showed no regression but rather progression of atherosclerosis. Whereas extract of A. aucheri significantly decreased atherosclerotic area in the aorta. Conclusion: These findings suggest that control diet without additional treatment cannot stop the progression of atherosclerosis. To use A. aucheri with control diet can stop progression of atherosclerosis and is effective for regression of atherosclerotic lesion.